Home quarantine: why the preference - Dkhar, Sabira Aalia; Quansar, Ruqia (International Journal Of Community Medicine And Public Health, 2020)
In the existing pandemic of COVID-19, we have been hearing a lot about quarantine. Quarantine is to isolate from normal relations and routine activities or communication and is recommended for apparently healthy people who may have been exposed to the virus (suspects) and may potentially transmit the same to others. These healthy individuals may fall sick due to possible exposure and are therefore advised to go on self-quarantine or may be ordered by state or local administration to stay at home or in facilities like hospitals (public or private), hotels, schools, worship places etc. to isolate them from normal relations in order to prevent transmission of virus to others. Quarantine can be unpleasant and lasts for 14 days which is the presumed incubation period for the virus.